Pengaruh Edukasi Pajak, Literasi Digital, Sistem E-Filing, Dan Tingkat Pendidikan Terhadap Kepatuhan Wajib Pajak Orang Pribadi (Studi Kasus Kantor Pajak Pratama Kudus) - Alamri, Nabila Rahmawati (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
This research aims to analyze the influence of tax education, digital literacy, e-filing system, and level of education on individual taxpayer compliance. This research was conducted at the Kudus Pratama Tax Service Office using quantitative methods. Data was collected through a purposive sampling questionnaire distributed to 400 taxpayers, then analyzed using multiple linear regression and obtained using the SPSS 25 tool. The research results showed that tax education and the e-filing system and level of education had a significant positive effect on taxpayer compliance. However, digital literacy does not have a significant effect on fulfilling individual tax obligations. These findings indicate that increasing tax education and optimizing the e-filing system as well as improving one's education can increase individual taxpayer compliance.